2008
DOI: 10.1002/bit.21885
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric particles conjugated with a ligand to VCAM‐1 exhibit selective, avid, and focal adhesion to sites of atherosclerosis

Abstract: The increased expression of VCAM-1 on endothelial segments within plaque regions could be used as a target to deliver polymeric drug carriers selectively to sites of atherosclerosis. We probed the hypothesis that polymeric particles conjugated with a ligand for VCAM-1 exhibit selective and avid adhesion to sites of atherosclerosis. Particles made from polystyrene or the biodegradable polymer poly(sebacic acid)-block-polyethylene glycol (PSA-PEG) were conjugated with an antibody to VCAM-1 (alpha-VCAM-1) or IgG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…When administered as an intravenous bolus, particles bound to ApoE -/-aortas in a 5 times higher amount when compared to wild type aortas with a selectivity for plaque regions, showing that the concept of targeted delivery can also be applied in the macro vasculature, where flow and adhesion dynamics differ significantly from those in the microvasculature. Closer inspection of the plaques showed that particles accumulated predominantly in the periphery of the plaques, which might be explained by higher focal VCAM-1 expression [56,57].…”
Section: Biodegradable Polymeric Particlesmentioning
confidence: 97%
“…When administered as an intravenous bolus, particles bound to ApoE -/-aortas in a 5 times higher amount when compared to wild type aortas with a selectivity for plaque regions, showing that the concept of targeted delivery can also be applied in the macro vasculature, where flow and adhesion dynamics differ significantly from those in the microvasculature. Closer inspection of the plaques showed that particles accumulated predominantly in the periphery of the plaques, which might be explained by higher focal VCAM-1 expression [56,57].…”
Section: Biodegradable Polymeric Particlesmentioning
confidence: 97%
“…10 Indeed, several molecular imaging applications of nanoparticle formulation targeted to VCAM-1 have been demonstrated, such as perfluorocarbons, 11,12 iron oxides, 13,14 polymers, 15 and quantum dots. 16 …”
mentioning
confidence: 99%
“…In addition to VCAM-1, various adhesion molecules (e.g., ICAM-1, E-selectin, and PECAM-1) have been implicated in atherosclerosis. 20,26 The fact that VCAM-1 has been shown to play a critical role in atherosclerosis and is highly expressed at the sites of atherosclerosis 12,20,22,26 led us to select VCAM-1 as the marker of inflammation in atherosclerosis. Our working hypothesis is that the endothelial cells that detach from an inflamed vascular site in atherosclerosis would exhibit a distinct VCAM-1 expression profile, generally higher than normal.…”
Section: Discussionmentioning
confidence: 99%
“…To characterize the phenotype of the detected endothelial cells, we focused on vascular cell adhesion molecule-1 (VCAM-1) which has been extensively studied with regard to atherosclerosis development and progression. 10,12,20,22,26 Indeed, VCAM-1 has been shown to be highly expressed at sites of atherosclerosis 12,22 and its expression by the endothelial cells within the plaque regions has been suggested as an important characteristic of the atherosclerotic phenotype. 23 The increased expression of VCAM-1 within the plaque regions is mainly due to the pro-inflammatory cytokines produced during atherogenesis.…”
Section: Introductionmentioning
confidence: 99%